(3dDdDI GdHMQjfs - (3GdOQGRj, GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s ((3GScfOQ Hf YjSi GdLRGFQjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYdfG ef Cgd GdQhGjI(B... (3CeG HYO, ajbhd(B... (3jhSa Hf CMeO Hf EHQGgje(B... (3Efg deG cGf ef fYeI Gddg(B...s
(3BNQgG (B:s
(3Cf GdcJH Gdefbhd efgG aj gPg GdELGRI ZjQ NGdjI Yf GdZdW ceG jfHF Yfg GdHjGV aj LedI ef GdehGVY(B... (3hjYXe GdhbY dgG aj UOhQ GdQGZHjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, U(B215s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B569s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B569s
(3GdCYdGe(B: (3L(B8(3, U(B215s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs